Visible-light-induced chemoselective reductive decarboxylative alkynylation under biomolecule-compatible conditions. Issue 25 (3rd October 2014) - Yang, Jie; Zhang, Jing; Qi, Li; Hu, Chenchen; Chen, Yiyun
Abstract : A visible-light-induced chemoselective reductive decarboxylative alkynylation for C(sp 3 )–C(sp) bond formation under biomolecule-compatible conditions. Abstract : We report a visible-light-induced reductive decarboxylative C(sp 3 )–C(sp) bond coupling reaction to construct aryl, alkyl and silyl substituted alkynes at room temperature in organic solvents or neutral aqueous solutions. This chemoselective alkynylation was compatible with various functional groups and biomolecules, and did not affect the protein enzyme activity.